Persepsi Petani Terhadap Sistem Sambung (Grafting) Dan Produksi Usahatani Kopi Robusta Di Kecamatan Dempo Utara Kota Pagaralam Provinsi Sumatera Selatan - Mirna Nanda Novita; Tubagus Hasanuddin; Dame Trully (Jurnal Ekonomi Pertanian dan Agribisnis, 2023)
Grafting coffee is one of the rejuvenation activities on unproductive plants to become productive with the aim of increasing production. This study aims to determine: 1) coffee farmers' perceptions of the grafting system in coffee cultivation, 2) coffee production produced before and after the grafting system in coffee cultivation, 3) factors related to farmers' perceptions on the Grafting system in coffee cultivation, 4) the relationship between coffee farmers' perceptions of the Grafting system and coffee production, 5) the relationship between coffee farmers' perceptions of the Grafting system and coffee farming income. This research was conducted in North Dempo District, Pagar Alam City, South Sumatra Province. This study is a quantitative study with a sample of 64 coffee farmers determined by the formula for determining the sample (Sugiarto, 2003). The research data collection was carried out from March to April 2022. The method used was a survey method. Research data were analyzed descriptively, parametric statistics, and non-parametric statistics. The results of this study stated that: 1) coffee farmers' perceptions of the grafting system in coffee cultivation were classified as quite good, 2) there was a significant difference in production from before applying the grafting system, which was 886.16 kg and after applying the grafting system, which was 1.753 kg. . 3) the factors that are significantly related to the perception of coffee farmers on the grafting system in coffee cultivation are the length of farming and the availability of entres, while age, education level, farmer knowledge, farmer social interaction and ownership status are not significantly related, 4) coffee farmers perception on the grafting system is not significantly related to the production of coffee farming 5) Coffee farmers' perception of the grafting system is not significantly related to coffee farming income.Â Keywords: Perception, Production, Coffee Grafting System